Perioperative problems in patients with brainstem tumors and their influence on patient outcome - Bharati, Sachidanand J (J Anaesthesiol Clin Pharmacol, 2016)
BACKGROUND AND AIMS: Patients with brainstem tumors have many associated systemic abnormalities and are prone to develop perioperative complications. We studied the problems associated with brainstem tumors and their influence on the postoperative neurological outcome. MATERIAL AND METHODS: Retrospective review of records of patients who underwent surgery for brainstem tumors over a period of 8 years was done. Preoperative variables, perioperative complications and neurological outcome as assessed by Glasgow Outcome Scale at the time of hospital discharge were noted. Association between perioperative factors and the unfavorable neurological outcome was evaluated. RESULTS: Data of 70 patients were retrieved, 7 patients were excluded from the study because of incomplete data and data analysis was carried out for 63 patients. We found that lower cranial nerve palsies (32%) and hydrocephalus (43%) were common preoperatively. Various intraoperative problems encountered were hemodynamic instability (56%), major blood loss requiring blood transfusion (40%) and venous air embolism (11%), and postoperative problems were meningitis (51%), hypokalemia (38%), chest infection (21%), seizure (11%), deterioration of Glasgow Coma Scale (GCS, 11%), hyponatremia (8%), hydrocephalus (6%), respiratory distress (3%) and operatives site hematoma (3%). Fifty-six (89%) patients had favorable outcome at hospital discharge whereas, 7 (11%) had an unfavorable outcome. There was no association between pre- and intra-operative factors and the neurological outcome. Deterioration of GCS, chest infection, and the need for reintubation and tracheostomy were associated with unfavorable neurological outcome. CONCLUSION: Patients of brainstem tumors are at increased risk of perioperative complications. Some of the postoperative complications were associated with unfavorable neurological outcome.